RELATIONSHIP BETWEEN TZI AND TZV WITH IPSS, QMAX, AND BOO - Satyagraha, Paksi; Djojodimedjo, Tarmono; Wirjopranoto, Soetojo; Budiono, Budiono (Indonesian Urological Association, 2013)
Objective: This study evaluate the relationship between the IPSS score, Qmax, and degree of bladder outlet obstruction with transitional zone volume (TZV) and transitional zone index (TZI) in clinical BPH patient. Material & Methods: This is an observational cross sectional study which 26 patients included with clinical BPH between September 2011 until January 2012. General information and other variables are recorded (total prostate volume, TZV, TZI, IPSS score, Qmax and degree of bladder outlet obstruction (BOO) according to Schaefer normogram. The data will be descriptive and analytically analyzed. Results: 26 patients with clinical BPH are included in this study, with average age is 64,7 (± 5,98) years. The average volume of the total prostate volume and TZV are 30,35 (± 15,35) gram and 15,31 (± 11,77) gram. Meanwhile the average of TZI is 0,4 (± 0,13). After the normal distribution test was performed, all data is analyzed with Pearson correlation test. A strong correlation was found between IPSS and total prostate volume (r = 0,526, p = 0,006), TZV (r = 0,671, p = 0,000) and TZI (r = 0,812, p = 0,000). A strong correlation is also found between TZI and BOO (r = 0,560, p = 0,003). Meanwhile weak correlation is found between Qmax and total prostate volume (r = -0,105, p = 0,608), TZV (r = -0,103, p = 0,616) and TZI (r = - 0,084, p = 0,734). Another weak correlation is shown between total prostate volume (r = 0,233, p = 0,253) and TZV (r = 0,37, p = 0,062) with degree of BOO according to Schaefer nomogram. Conclusion: TZV has significant correlation with IPSS score, but no significant correlation with Qmax and degree of BOO in patients with clinical BPH. Meanwhile TZI has a significant correlation with IPSS and degree of BOO in patients with clinical BPH. TZI could be performed as a single non invasive procedure to determine BOO in patients with clinical BPH.Keywords: Prostatic hyperplasia, transition zone, ultrasonography, urodynamics.